2012
DOI: 10.1002/mds.25129
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists and delusional jealousy in Parkinson's disease: A cross‐sectional prevalence study

Abstract: These findings suggest that dopamine agonist treatment represents a risk factor for DJ in PD independent of the presence of a dementing disorder, and the presence of this additional nonmotor side effect should be investigated in this clinical population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…1,2 Delusional jealousy may be observed in many psychiatric disorders, but previous clinical reports have noted the association of this morbid condition in several organic psychoses, including stroke, 3,4 Parkinson's disease, 5,6 traumatic brain injury, 7 and dementia. 8 Soyka et al 9 found that the prevalence of delusional jealousy was highest in organic psychoses (7.0%), followed by paranoid disorders (6.7%), alcohol psychosis (5.6%), and schizophrenia (2.5%); whereas in affective disorder, delusional jealousy was found in only 0.1% of patients.…”
mentioning
confidence: 99%
“…1,2 Delusional jealousy may be observed in many psychiatric disorders, but previous clinical reports have noted the association of this morbid condition in several organic psychoses, including stroke, 3,4 Parkinson's disease, 5,6 traumatic brain injury, 7 and dementia. 8 Soyka et al 9 found that the prevalence of delusional jealousy was highest in organic psychoses (7.0%), followed by paranoid disorders (6.7%), alcohol psychosis (5.6%), and schizophrenia (2.5%); whereas in affective disorder, delusional jealousy was found in only 0.1% of patients.…”
mentioning
confidence: 99%
“…DJ has been reported in medicated PD patients [2,10,11] but in contrast to HS, no studies directly investigated the neural bases of DJ in PD patients. However, fMRI studies in healthy subjects highlighted the role of dopaminergic fronto-striatal networks in motivating individuals to pair-bonding [4]; in particular, the insula and the dopaminergic circuits linking basal ganglia and the ventromedial prefrontal cortex (vmPFC) would mainly be involved in the evaluation of the rewarding nature of the social bonds and in the representation of associated emotions and somatic sensations, generally providing an affective meaning to the relationship with the partner.…”
Section: Discussionmentioning
confidence: 91%
“…We prolonged our previous cross-sectional investigation of ICDs and DJ [1,2], screened with the Questionnaire for Impulsive Compulsive Disorders in Parkinson's disease [6] and the Parkinson's Psychosis Questionnaire [7], until the recruitment of 1063 consecutive PD patients attending the Movement Disorder Tertiary Clinic of the Hospital of Viareggio, Italy. We did not include newly diagnosed drug-naïve PD patients or patients with clinical signs and neuroimaging findings suggestive of either secondary parkinsonism or primary atypical parkinsonism, such as Lewy body dementia, multiple system atrophy, progressive supranuclear palsy, and corticobasal degeneration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies covering the EU-5 nations, reported rates of hallucinations and delusions among patients with PD ranged from 10-45% in France, [34][35][36] 13-29% in Germany, 37,38 11-32% in Italy, [39][40][41] 15-42% in Spain 42,43 and 13-55% in the UK. 17,[44][45][46] These broad reported ranges highlight the difficulty of carrying out cross-study comparisons.…”
Section: Disruptiveness and Comorbidity Ratesmentioning
confidence: 99%